Rethinking knowledge systems in psychology: addressing epistemic hegemony and systemic obstacles in climate change studies - Aziz, Mudassar; Anjum, Gulnaz (Frontiers in Psychology, 2025)
Climate psychology has emerged as a critical field examining how individuals and societies perceive, respond to, and engage with the climate crisis. However, the discipline remains deeply influenced by Western epistemologies, which privilege individualistic, anthropocentric, and positivist approaches to knowledge production. This perspective paper critically examines how Western bias shapes the theoretical frameworks, methodological approaches, and policy implications within climate psychology, often to the exclusion of non-Western epistemologies, particularly those from Indigenous and Global South communities. We argue that dominant Western paradigms, rooted in individualism, cognitive-behavioral models, and human-exceptionalist perspectives, constrain the field's ability to fully capture the complex, relational, and context-specific ways in which diverse populations engage with climate change. Moreover, the overreliance on quantitative and experimental methodologies systematically marginalizes Indigenous methodologies, such as storytelling, relational worldviews, and participatory research approaches, thereby limiting the inclusivity and ecological validity of climate psychology research. To address these limitations, we propose a decolonial approach to climate psychology, advocating for the integration of Indigenous epistemologies, pluralistic methodologies, and equitable research collaborations. By diversifying epistemic foundations and methodological tools, climate psychology can move beyond its Western biases, leading to more culturally responsive research and more effective and just climate interventions. This paper calls for a fundamental reorientation in climate psychology, one that values epistemic diversity as essential for addressing the multifaceted human dimensions of climate change.